Lethal Lpg Exposure a Case Report - Kurtuluş, Ayşe; Acar, Kemalettin; Boz, Bora; Kelten, Canan (The Bulletin of Legal Medicine, 2009)
LPG (liquefied petroleum gases) is a mixture of petroleum and natural gases that exist in a liquid state at ambient temperatures when under moderate pressures. It includes light aliphatic hydrocarbons n-butane (C4H10) and propane (CjHg). While deaths depending on inhaling LPG are usually accidental, suicidal deaths may be seen rarely. Deaths occur in four mechanisms as asphyxia, vagal inhibition, respiratory depression and arrhythmia. In this study, a 64-year-old male case is presented who committed suicide by using a specific contrivance. The body was found in bed under entirely covered by two layers of blanket and there was a hose from an LPG cylinder to bottom of blankets. We discussed postmortem macroscopically and microscopically findings in view of the literature. Key words: LPG, n-butane, propane, suicide, forensic pathology